Termiticidal and Nematicidal activities of five extracts from Garlic (Allium sativum). Issue 1 (May 2021) - Khairan, K; Aulina,; Yusra, N; Eriana, C N; Bahi, M; Syaukani, S; Sriwati, R; Jacob, C
Abstract: Garlic ( Allium sativum Linn) has been known and used as therapeutic agents to prevent several pathologies diseases. The aim of this study is to evaluate the effects of five garlic extracts, namely, aqueous garlic extract (AGE), methanol garlic extract (MGE), ethyl acetate garlic extract, EAGE), and n -hexane garlic extract (HGE) against root-knot nematode, Meloidogyne sp. and termite, Nasutitermes sp. The nematicidal and termiticidal activities of five garlic extracts were performed at concentration of 10; 25; and 50%. The nematicidal assay revealed that aqueous garlic extract (AGE) and ethyl acetate garlic extract (EAGE) have higher activities against Melodogyne sp at all concentrations tested at 5 h of time incubation with the percentages of viabilities between 4.67%-15.63% and 0%-10.23% respectively. Meanwhile, the termiticidal assay results showed that aqueous garlic extract (AGE), ethyl acetate garlic extract (EAGE), and n -hexane garlic extract (HGE) have stronger activity against Melodogyne sp at all concentrations tested at 8 h of time incubation with the percentages of viabilities of the extracts were 0%. Overall, the results showed that ethyl acetate garlic extract (EAGE) has highest activity against Meloidogyne sp, while the n-hexane garlic extract (HGE) has strongest activity against Nasutitermes sp.